The Nature of Revolution on Animal Farm - Goran Omar Mustafa (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
ABSTRACT Revolution as a phenomenon is considered as a way to a complete change of a situation or system of government to a better one. Dose revolution really is the right way to fulfil our dreams and have a better way of life? Or simply it is just changing the face of rulers or the name of the governments. Many writers and novelists wrote about this issue. George Orwell which is considered as apolitical writer, is one of them. He wrote many novels. Animal Farm, as one of them, is an allegorical story of some animals in a farm. They begin a revolution against the humans with the dream of getting rid of Man as the root cause of their problems, and to be rich and free. They have a short period of honeymoon revolution, but then their dream of building a utopian farm crashes by the pigs and would find themselves in dystopia. This paper aims to study the nature of revolution generally in the shed light of human history. Then to explore how this phenomenon is treated by Orwell in his novel. Can we consider revolution as a right way to have a complete change in the political system and thinking of people? The researchers try to illuminate and find answer for those questions by providing examples from the story of Animal Farm.